Enhancement of damping response in polymers and composites by the addition of graphene nanoplatelets. (18th August 2022) - Katsiropoulos, Ch.V.; Pappas, P.; Koutroumanis, N.; Kokkinos, A.; Galiotis, C.
Abstract: The damping characteristics of advanced lightweight composites are of paramount importance for a variety of applications particularly those employing composite parts or components operating under dynamic external loading. Graphene has been shown to possess high stiffness and strength and is widely esteemed as an ideal additive for enhancing the mechanical properties of polymeric, ceramic and even metallic composite matrices. However, it has been postulated that if such behaviour can be combined with increased fracture toughness and damping characteristics then a whole new class of multifunctional composites could emerge. In this work the damping response of carbon fibre/polymer composites (CFRPs) whose matrix is doped with graphene nanoplatelets (GNPs) at various concentrations, is examined in detail. The results presented here indicate that the addition of GNPs into both the neat polymer and the CFRP, affects significantly the damping behaviour. In particular, for the CFRP a significant increase of damping capacity is observed for low concentrations in the range of 0.15–1 wt%, whereas for higher concentrations the corresponding enhancement does not follow a clear trend. Plausible explanation for this behaviour is presented herein. Graphical abstract: Image 1 Highlights: The Damping response of carbon fibre/polymer composites whose matrix is doped with graphene nanoplatelets is investigated. A new tailor-made experimental setup was developed and utilized. Significant effect of the GNPs addition to the damping behaviour. DMA testing also confirms the free oscillation results. Specific surface calculations and SEM tests provide evidence of the mechanisms that govern the damping behaviour.